A ternary co-blended lithium manganese iron phosphate material and its preparation method and application

By blending lithium manganese iron phosphate and ternary single crystal materials in ternary polycrystalline materials to adjust the particle size distribution, the problem of differences in circulation and safety performance of ternary materials in lithium-ion batteries is solved, and the stability of the material is improved and cycle performance, achieving higher energy density and battery performance.

CN115799481BActive Publication Date: 2024-12-13EVE POWER CO LTD

Patent Information

Application Number
CN202211651707.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2024-12-13
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

There are differences in the circulation and safety performance of existing ternary polycrystalline and single crystal materials in lithium-ion batteries, and the cost and process requirements are high, making it difficult to take into account both performance and safety.

Method used

Blending lithium manganese iron phosphate and ternary single crystal materials into ternary polycrystalline materials, adjusting the particle size distribution to make it between ternary polycrystalline and lithium manganese iron phosphate, and improving the overall particle size distribution width of the material. Enhance the stability of lithium ions during charging and discharging and the elastic strain ability of external forces to impact.

Benefits of technology

Through the adjustment of particle size distribution, the safety and circulation performance of the material are improved, the overall performance of lithium-ion batteries is improved, and higher energy density and better battery performance are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115799481B_ABST
    Figure CN115799481B_ABST
Patent Text Reader

Abstract

The present invention relates to a ternary co-blended lithium iron manganese phosphate material and a preparation method and application thereof, wherein the ternary co-blended lithium iron manganese phosphate material comprises a ternary single crystal material, a ternary polycrystalline material and lithium iron manganese phosphate; the particle size distribution of the ternary single crystal material is between that of the ternary polycrystalline material and the lithium iron manganese phosphate. The particle size distribution of the ternary single crystal material in the present invention is between that of the large particles of the ternary polycrystalline material and the small particles of the lithium iron manganese phosphate. After blending, the particle size distribution of the material is wider, and particles with relatively small particle sizes can fill the gaps between the large particles, thereby improving the compaction density of the material to a certain extent; according to the particle size distribution, the overall particle size distribution of the lithium iron manganese phosphate material co-blended with the ternary polycrystalline and ternary single crystal materials becomes wider, thereby improving the stability of lithium ions in the process of charging and discharging in and out of the lattice of the ternary material, providing elastic strain for the material to be impacted by external forces, thereby improving the safety and cycle performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ternary positive electrode material manufacturing, and relates to a ternary co-blended lithium manganese iron phosphate material, and in particular to a ternary co-blended lithium manganese iron phosphate material and a preparation method and application thereof. Background Art

[0002] Humans need renewable energy to replace fossil fuels and reduce carbon dioxide emissions. Advanced energy storage materials are the trend of future development. Lithium-ion batteries have excellent energy density and cycle durability, and are lightweight, which can meet our growing energy needs. The study of lithium batteries is a hot topic in current research in physics, chemistry, and materials. The commonly used lithium battery positive electrode materials in the market are lithium cobalt oxide, ternary, lithium iron phosphate, and lithium manganese iron phosphate.

[0003] Different positive electrode materials have different advantages and disadvantages due to the structural characteristics of their own materials. Ternary polycrystals exist in the form of secondary particle agglomerates at the micron level, with high capacity and good rate performance. However, there are a large number of grain boundaries inside the secondary particle agglomerates. During the battery charging and discharging process, the lattice constant and unit cell volume change, generating anisotropic stress, resulting in secondary particle breakage. This ultimately leads to a rapid increase in side reactions, an increase in impedance, and a rapid decrease in cycle performance. Compared with polycrystalline, ternary single crystals have better mechanical strength, which inhibits particle breakage, fewer side reactions, and a stable material structure. Therefore, the cycle and thermal stability of single crystals are higher than those of polycrystalline, and the high voltage resistance of ternary single crystals is also better than that of polycrystalline. However, ternary single crystals have higher process requirements, and the cost is higher than that of ternary polycrystalline. At the same time, the rate performance and capacity of ternary single crystals under the same voltage conditions are not as good as those of ternary polycrystalline. Lithium manganese iron phosphate is a new type of phosphate lithium-ion battery positive electrode material formed by doping a certain proportion of manganese on the basis of lithium iron phosphate. Lithium manganese iron phosphate maintains the stable olivine structure of lithium iron phosphate, and its structure is more stable during the charging and discharging process. Even if all lithium ions are embedded during the charging process, the structure will not collapse, so it is safer and has lower costs. The application of pure lithium manganese iron phosphate has obvious cost advantages, safety performance and higher energy density than ternary materials, and its main limitation is low conductivity.

[0004] In order to balance performance and safety, the ternary material is combined with lithium manganese iron phosphate materials to further integrate the advantages of the materials, complement each other's shortcomings through the combination, improve energy density, and have more comprehensive and integrated battery performance. However, due to the large difference between polycrystalline and single crystal ternary materials, it will affect and restrict the cycle and safety performance.

[0005] Therefore, how to provide a composite material is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a ternary co-blended lithium iron manganese phosphate material and a preparation method and application thereof. On the basis of blending lithium iron manganese phosphate into the ternary polycrystal, a ternary single crystal material is further blended. According to the particle size distribution, the overall particle size distribution of the lithium iron manganese phosphate material co-blended with the ternary polycrystal and the ternary single crystal material becomes wider, which improves the stability of lithium ions entering and exiting the ternary material lattice during charging and discharging, provides elastic strain for the material when it is impacted by external force, and thus comprehensively improves the safety and cycle performance of the blended material.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a ternary co-blended lithium iron manganese phosphate material, wherein the ternary co-blended lithium iron manganese phosphate material comprises a ternary single crystal material, a ternary polycrystalline material and lithium iron manganese phosphate;

[0009] The particle size distribution of the ternary single crystal material is between that of the ternary polycrystalline material and lithium manganese iron phosphate.

[0010] Particle size distribution refers to the uniformity of the particle size of the material, while particle size refers to a single particle in the material. The overall particle size distribution of the material can be adjusted by blending single particles of different sizes.

[0011] Those skilled in the art should know that the particle size distribution of the ternary single crystal material is smaller than the particle size distribution of the ternary polycrystalline material.

[0012] The particle size distribution of the ternary single crystal material in the present invention is between the large particles of the ternary polycrystalline material and the small particles of the lithium iron manganese phosphate. After blending, the particle size distribution of the material is wider, and the particles with relatively small particle sizes can fill the gaps between the large particles, thereby improving the compaction density of the material to a certain extent. According to the particle size distribution, the overall particle size distribution of the lithium iron manganese phosphate material co-blended with the ternary polycrystalline and ternary single crystal materials becomes wider, thereby improving the stability of lithium ions in the process of charging and discharging entering and exiting the lattice of the ternary material, providing elastic strain for the material when it is impacted by external forces, thereby improving the safety and cycle performance of the material.

[0013] Preferably, the median particle size of the ternary single crystal material is 4 to 7 μm, for example, 4 μm, 4.5 μm, 5 μm, 6 μm, 6.5 μm or 7 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Preferably, the particle size distribution of the ternary single crystal material is 0.3 to 0.8, for example, it can be 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the median particle size of the ternary polycrystalline material is 10 to 20 μm, for example, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] Preferably, the particle size distribution of the ternary polycrystalline material is 0.8-1.2, for example, it can be 0.8, 0.9, 1, 1.1 or 1.2, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] Preferably, the median particle size of the lithium manganese iron phosphate is 1 to 2 μm, for example, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm or 2 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the particle size distribution of the lithium manganese iron phosphate is 0.2-0.4, for example, it can be 0.2, 0.25, 0.3, 0.35 or 0.4, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0019] Preferably, the mass relationship among the ternary single crystal material, the ternary polycrystalline material and the lithium manganese iron phosphate in the ternary co-blended lithium manganese iron phosphate material is distributed according to the gradation formula:

[0020] C / (A+B)=α / (1-α), 0.5≤α<1, for example, it can be 0.5, 0.6, 0.7, 0.8 or 0.9, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] A / B=β / (1-β), 0.6≤β<1, for example, it can be 0.6, 0.7, 0.8, 0.9 or 0.95, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0022] Among them, A is the mass of the ternary polycrystalline material, B is the mass of the ternary single crystal material, and C is the mass of the lithium iron manganese phosphate.

[0023] By grading the materials, the proportions can be determined quickly and accurately, thereby producing positive electrode materials with more comprehensive and integrated battery performance.

[0024] Preferably, the method for preparing the ternary single crystal material comprises the following steps:

[0025] (a) mixing a nickel-cobalt-manganese hydroxide precursor, a lithium source and a first additive, and performing a first sintering to obtain a ternary single crystal first sintered material;

[0026] (b) mixing the ternary single crystal first sintering material and the second additive, and performing a second sintering to obtain the ternary single crystal material.

[0027] The ternary single crystal material provided by the present invention has high mechanical strength and few grain boundaries, and can maintain the structural stability of the material during the cycle. The ternary single crystal material is co-blended with polycrystalline and lithium manganese iron phosphate to improve the structural stability of the material, reduce the occurrence of interface side reactions during the cycle, and improve the cycle performance of the material.

[0028] Preferably, the first additive in step (a) comprises any one of strontium carbonate, aluminum oxide, zirconium hydroxide, zirconium dioxide, lithium nitrate, magnesium dioxide, niobium oxide, yttrium trioxide, aluminum phosphate or tungsten trioxide, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of strontium carbonate and aluminum oxide, a combination of aluminum oxide and zirconium hydroxide, a combination of zirconium hydroxide and zirconium dioxide, a combination of zirconium dioxide and lithium nitrate, a combination of lithium nitrate and magnesium dioxide, a combination of magnesium dioxide and niobium oxide, a combination of niobium oxide and yttrium trioxide, a combination of yttrium trioxide and A combination of aluminum phosphate, a combination of aluminum phosphate and tungsten trioxide, a combination of strontium carbonate, aluminum oxide and zirconium hydroxide, a combination of zirconium hydroxide, zirconium dioxide and lithium nitrate, a combination of lithium nitrate, magnesium dioxide and niobium oxide, a combination of niobium oxide, yttrium trioxide and aluminum phosphate, a combination of yttrium trioxide, aluminum phosphate and tungsten trioxide, a combination of strontium carbonate, aluminum oxide, zirconium hydroxide, zirconium dioxide and lithium nitrate, a combination of zirconium hydroxide, zirconium dioxide, lithium nitrate, magnesium dioxide and niobium oxide, or a combination of magnesium dioxide, niobium oxide, yttrium trioxide, aluminum phosphate and tungsten trioxide.

[0029] Preferably, the temperature of the first sintering in step (a) is 750-950°C, for example, 750°C, 800°C, 850°C, 900°C or 950°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, the first sintering time in step (a) is 10 to 15 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] Preferably, the second additive in step (b) comprises any one of metal fluorides, lithium compounds, silicates, phosphates or oxides, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of fluorides and lithium compounds, a combination of lithium compounds and silicates, a combination of silicates and phosphates, a combination of phosphates and oxides, a combination of fluorides, lithium compounds and silicates, a combination of lithium compounds, silicates and phosphates, a combination of silicates, phosphates and oxides, a combination of fluorides, lithium compounds, silicates and phosphates, a combination of lithium compounds, silicates, phosphates and oxides, or a combination of fluorides, lithium compounds, silicates, phosphates and oxides.

[0032] Preferably, the metal includes any one of V, Al, Zn, Zr, Ti, Mg, Ru, La or Ce, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of V and Al, a combination of Al and Zn, a combination of Zn and Zr, a combination of Zr and Ti, a combination of Ti and Mg, a combination of Mg and Ru, a combination of Ru and La, a combination of La and Ce, a combination of V, Al and Zn, a combination of Zr, Ti and Mg, a combination of Ru, La and Ce, a combination of V, Al, Zn and Zr, a combination of Zn, Zr, Ti and Mg, a combination of Ti, Mg, Ru and La, a combination of Mg, Ru, La and Ce, a combination of V, Al, Zn, Zr, Ti and Mg, or a combination of Ti, Mg, Ru, La and Ce.

[0033] Preferably, the temperature of the second sintering in step (b) is 400-500°C, for example, 400°C, 420°C, 440°C, 460°C, 480°C or 500°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the second sintering time in step (b) is 3 to 6 hours, for example, 3 hours, 3.5 hours, 4 hours, 5 hours, 5.5 hours or 6 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the method for preparing the ternary polycrystalline material comprises the following steps:

[0036] Mixing nickel-cobalt-manganese hydroxide precursor, lithium source and additive materials, calcining at high temperature to obtain ternary polycrystalline material;

[0037] Preferably, the additive material includes any one of strontium carbonate, aluminum oxide, zirconium hydroxide, zirconium dioxide, lithium nitrate, magnesium dioxide, niobium oxide, yttrium trioxide, aluminum phosphate or tungsten trioxide, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of strontium carbonate and aluminum oxide, a combination of aluminum oxide and zirconium hydroxide, a combination of zirconium hydroxide and zirconium dioxide, a combination of zirconium dioxide and lithium nitrate, a combination of lithium nitrate and magnesium dioxide, a combination of magnesium dioxide and niobium oxide, a combination of niobium oxide and yttrium trioxide, a combination of yttrium trioxide and aluminum phosphate. a combination of strontium carbonate, aluminum oxide and zirconium hydroxide, a combination of zirconium hydroxide, zirconium dioxide and lithium nitrate, a combination of lithium nitrate, magnesium dioxide and niobium oxide, a combination of niobium oxide, yttrium trioxide and aluminum phosphate, a combination of yttrium trioxide, aluminum phosphate and tungsten trioxide, a combination of strontium carbonate, aluminum oxide, zirconium hydroxide, zirconium dioxide and lithium nitrate, a combination of zirconium hydroxide, zirconium dioxide, lithium nitrate, magnesium dioxide and niobium oxide, or a combination of magnesium dioxide, niobium oxide, yttrium trioxide, aluminum phosphate and tungsten trioxide.

[0038] Preferably, the high temperature calcination temperature is 750-950°C, for example, 750°C, 800°C, 850°C, 900°C or 950°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] Preferably, the high temperature calcination time is 10 to 15 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Preferably, the high-temperature calcination further includes rolling, jaw crushing, pulverizing and screening.

[0041] Preferably, the method for preparing lithium manganese iron phosphate comprises the following steps:

[0042] (i) in a liquid phase system, mixing a lithium iron manganese phosphate precursor, a lithium source and a carbon source, and drying to obtain a lithium iron manganese phosphate precursor;

[0043] (ii) Sintering in an inert gas atmosphere to obtain lithium iron manganese phosphate.

[0044] Preferably, the drying in step (i) comprises spray drying.

[0045] Preferably, the sintering temperature in step (ii) is 500-800°C, for example, 500°C, 550°C, 600°C, 700°C or 800°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0046] Preferably, the sintering time in step (ii) is 5 to 18 hours, for example, 5 hours, 8 hours, 10 hours, 15 hours or 18 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0047] Preferably, the lithium iron manganese phosphate is carbon-coated lithium iron manganese phosphate.

[0048] In a second aspect, the present invention provides a method for preparing a ternary co-blended lithium manganese iron phosphate material, the preparation method comprising the following steps:

[0049] According to a grading formula, a ternary single crystal material, a ternary polycrystalline material and lithium iron manganese phosphate are mixed to obtain the ternary co-blended lithium iron manganese phosphate material;

[0050] The gradation formula is:

[0051] C / (A+B)=α / (1-α), 0.5≤α<1,

[0052] A / B=β / (1-β), 0.6≤β<1.

[0053] The mixing requires that the three materials are evenly dispersed.

[0054] In a third aspect, the present invention provides a positive electrode sheet, wherein the positive electrode sheet contains the ternary co-blended lithium manganese iron phosphate material as described in the first aspect.

[0055] In a fourth aspect, the present invention provides a battery comprising the ternary co-blended lithium manganese iron phosphate material as described in the first aspect.

[0056] According to the above technical scheme, the beneficial effects of the present invention are as follows:

[0057] The particle size distribution of the ternary single crystal material in the present invention is between the large particles of the ternary polycrystalline material and the small particles of the lithium iron manganese phosphate. After blending, the particle size distribution of the material is wider, and the particles with relatively small particle sizes can fill the gaps between the large particles, thereby improving the compaction density of the material to a certain extent. According to the particle size distribution, the overall particle size distribution of the lithium iron manganese phosphate material co-blended with the ternary polycrystalline and ternary single crystal materials becomes wider, thereby improving the stability of lithium ions in the process of charging and discharging entering and exiting the lattice of the ternary material, providing elastic strain for the material when it is impacted by external forces, thereby improving the safety and cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 This is a scanning electron microscope image of the ternary single crystal material in Example 1.

[0059] Figure 2 This is a scanning electron microscope image of the ternary polycrystalline material in Example 1.

[0060] Figure 3 This is a scanning electron microscope image of the lithium manganese iron phosphate in Example 1. DETAILED DESCRIPTION

[0061] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0062] Example 1

[0063] This embodiment provides a ternary co-blended lithium manganese iron phosphate material, wherein the ternary co-blended lithium manganese iron phosphate material is composed of a ternary single crystal material (Scanning electron microscope as shown in FIG. Figure 1 As shown), ternary polycrystalline materials (SEM as shown Figure 2 As shown) and lithium manganese iron phosphate (SEM as Figure 3 The mass relationship is distributed according to the grading formula:

[0064] C / (A+B)=α / (1-α), α=0.8,

[0065] A / B = β / (1-β), β = 0.7,

[0066] A is the mass of the ternary polycrystalline material, B is the mass of the ternary single crystal material, and C is the mass of the lithium iron manganese phosphate; illustratively, A=0.7kg, B=0.3kg, C=4kg, A, B and C are only examples, and other masses that satisfy the grading formula are within the scope of this embodiment.

[0067] The ternary co-blended lithium manganese iron phosphate material is prepared by the following method:

[0068] According to a grading formula, a ternary single crystal material, a ternary polycrystalline material and lithium iron manganese phosphate are mixed to obtain the ternary co-blended lithium iron manganese phosphate material;

[0069] The ternary single crystal material is prepared by the following method:

[0070] (a) mixing NCM523 nickel-cobalt-manganese hydroxide precursor, lithium hydroxide and strontium carbonate, and performing a first sintering at 850° C. for 12 h to obtain a ternary single crystal first sinter;

[0071] (b) Mixing the ternary single crystal first sinter and V2O5, performing a second sintering at 450°C for 5 hours, rolling, jaw crushing, crushing and screening to obtain a ternary single crystal material, wherein the median particle size of the ternary single crystal material is 5 μm and the particle size distribution is 0.5.

[0072] The ternary polycrystalline material is prepared by the following method:

[0073] Mix NCM523 nickel-cobalt-manganese hydroxide precursor, lithium hydroxide and aluminum phosphate, calcine at 850° C. for 12 hours, roll, jaw crusher, crush and screen to obtain a ternary polycrystalline material, wherein the median particle size of the ternary polycrystalline material is 15 μm and the particle size distribution is 1;

[0074] The lithium manganese iron phosphate is prepared by the following method:

[0075] (i) in a liquid phase system, mixing a lithium iron manganese phosphate precursor, lithium hydroxide and glucose, and spray drying to obtain a lithium iron manganese phosphate precursor;

[0076] (ii) Sintering in an inert gas atmosphere to obtain lithium iron manganese phosphate, wherein the lithium iron manganese phosphate is carbon-coated lithium iron manganese phosphate, has a median particle size of 1.5 μm, and a particle size distribution of 0.3.

[0077] Example 2

[0078] This embodiment provides a ternary co-blended lithium iron manganese phosphate material, which is composed of a ternary single crystal material, a ternary polycrystalline material and lithium iron manganese phosphate, and the mass relationship is distributed according to the grading formula:

[0079] C / (A+B)=α / (1-α), α=0.5,

[0080] A / B = β / (1-β), β = 0.6,

[0081] A is the mass of ternary polycrystalline material, B is the mass of ternary single crystal material, and C is the mass of lithium manganese iron phosphate;

[0082] The ternary co-blended lithium manganese iron phosphate material is prepared by the following method:

[0083] According to a grading formula, a ternary single crystal material, a ternary polycrystalline material and lithium iron manganese phosphate are mixed to obtain the ternary co-blended lithium iron manganese phosphate material;

[0084] The ternary single crystal material is prepared by the following method:

[0085] (a) mixing NCM523 nickel-cobalt-manganese hydroxide precursor, lithium nitrate and zirconium hydroxide, and performing a first sintering at 750° C. for 15 h to obtain a ternary single crystal first sinter;

[0086] (b) Mixing the ternary single crystal first sinter and magnesium silicate, performing a second sintering at 400° C. for 6 hours, and rolling, jaw crushing, crushing and screening to obtain a ternary single crystal material, wherein the median particle size of the ternary single crystal material is 4 μm and the particle size distribution is 0.3.

[0087] The ternary polycrystalline material is prepared by the following method:

[0088] Mix NCM523 nickel-cobalt-manganese hydroxide precursor, lithium nitrate and niobium oxide, calcine at 750° C. for 15 hours, roll, jaw crusher, crush and screen to obtain a ternary polycrystalline material, wherein the median particle size of the ternary polycrystalline material is 10 μm and the particle size distribution is 0.8;

[0089] The lithium manganese iron phosphate is prepared by the following method:

[0090] (i) in a liquid phase system, mixing a lithium iron manganese phosphate precursor, lithium nitrate and starch, and spray drying to obtain a lithium iron manganese phosphate precursor;

[0091] (ii) Sintering in an inert gas atmosphere to obtain lithium iron manganese phosphate, wherein the lithium iron manganese phosphate is carbon-coated lithium iron manganese phosphate, has a median particle size of 1 μm, and a particle size distribution of 0.2.

[0092] Example 3

[0093] This embodiment provides a ternary co-blended lithium iron manganese phosphate material, which is composed of a ternary single crystal material, a ternary polycrystalline material and lithium iron manganese phosphate, and the mass relationship is distributed according to the grading formula:

[0094] C / (A+B)=α / (1-α), α=0.9,

[0095] A / B = β / (1-β), β = 0.9,

[0096] A is the mass of ternary polycrystalline material, B is the mass of ternary single crystal material, and C is the mass of lithium manganese iron phosphate;

[0097] The ternary co-blended lithium manganese iron phosphate material is prepared by the following method:

[0098] According to a grading formula, a ternary single crystal material, a ternary polycrystalline material and lithium iron manganese phosphate are mixed to obtain the ternary co-blended lithium iron manganese phosphate material;

[0099] The ternary single crystal material is prepared by the following method:

[0100] (a) mixing NCM523 nickel-cobalt-manganese hydroxide precursor, lithium acetate and magnesium dioxide, and performing a first sintering at 950° C. for 10 h to obtain a ternary single crystal first sinter;

[0101] (b) Mixing the ternary single crystal first sinter and zinc fluoride, performing a second sintering at 500° C. for 3 hours, rolling, jaw crushing, crushing and screening to obtain a ternary single crystal material, wherein the median particle size of the ternary single crystal material is 7 μm and the particle size distribution is 0.8.

[0102] The ternary polycrystalline material is prepared by the following method:

[0103] Mix NCM523 nickel-cobalt-manganese hydroxide precursor, lithium acetate and yttrium trioxide, calcine at 950° C. for 10 hours, roll, jaw crusher, crush and screen to obtain a ternary polycrystalline material, wherein the median particle size of the ternary polycrystalline material is 20 μm and the particle size distribution is 1.2;

[0104] The lithium manganese iron phosphate is prepared by the following method:

[0105] (i) in a liquid phase system, mixing a lithium iron manganese phosphate precursor, lithium acetate and citric acid, and spray drying to obtain a lithium iron manganese phosphate precursor;

[0106] (ii) Sintering in an inert gas atmosphere to obtain lithium iron manganese phosphate, wherein the lithium iron manganese phosphate is carbon-coated lithium iron manganese phosphate, has a median particle size of 2 μm, and a particle size distribution of 0.4.

[0107] Example 4

[0108] This embodiment provides a ternary co-blended lithium manganese iron phosphate material, which differs from Embodiment 1 in that α=0.4.

[0109] Example 5

[0110] This embodiment provides a ternary co-blended lithium manganese iron phosphate material, which differs from Embodiment 1 in that β=0.5.

[0111] Example 6

[0112] This embodiment provides a ternary co-blended lithium manganese iron phosphate material, which differs from Embodiment 1 in that the median particle size of the ternary single crystal is 8 μm.

[0113] Example 7

[0114] This embodiment provides a ternary co-blended lithium manganese iron phosphate material, which is different from Embodiment 1 in that the median particle size of the ternary single crystal material is 2 μm.

[0115] Comparative Example 1

[0116] This comparative example provides a ternary co-blended lithium iron manganese phosphate material, which is different from Example 1 in that the ternary co-blended lithium iron manganese phosphate material is composed of a ternary polycrystalline material and lithium iron manganese phosphate.

[0117] C / A=α / (1-α), α=0.8,

[0118] A is the mass of the ternary polycrystalline material, and C is the mass of lithium manganese iron phosphate.

[0119] Comparative Example 2

[0120] This comparative example provides a ternary co-blended lithium manganese iron phosphate material, which differs from Example 1 in that the particle size distribution of the ternary single crystal material is the same as that of the lithium manganese iron phosphate.

[0121] Comparative Example 3

[0122] This comparative example provides a ternary co-blended lithium manganese iron phosphate material, which is different from Example 1 in that the particle size distribution of the lithium manganese iron phosphate is between that of the ternary single crystal material and the ternary polycrystalline material.

[0123] The positive electrode material was used to make a positive electrode sheet, and a lithium-ion battery was assembled according to GB 31241-2014 and tested.

[0124] Test conditions:

[0125] Gram capacity test: 25℃, constant current and constant voltage charging at 0.2C to 4.2V, cut off at 0.02C, and DC discharge at 0.2C to 2.5V.

[0126] Cycle test: 25℃, 2.5-4.2V, 1C / 1C cycle.

[0127] The test results are shown in Table 1.

[0128] Table 1

[0129]

[0130]

[0131] The following conclusions can be drawn from Table 1:

[0132] (1) It can be seen from Examples 1-3 and Comparative Example 1 that the present invention provides a ternary co-blended lithium iron manganese phosphate material and a preparation method and application thereof. On the basis of blending lithium iron manganese phosphate into a ternary polycrystalline, a ternary single crystal material is further blended. According to the particle size distribution, the overall particle size distribution of the lithium iron manganese phosphate material co-blended with the ternary polycrystalline and the ternary single crystal material becomes wider, thereby increasing the compaction density of the blended material and improving the stability of lithium ions in the process of charging and discharging when entering and exiting the lattice of the ternary material, thereby providing elastic strain for the material when it is impacted by external forces, thereby comprehensively improving the safety and cycle performance of the blended material.

[0133] (2) From the comparison between Examples 4 and 5 and Example 1, it can be seen that according to the grading formula provided by the present invention, the ternary co-blended lithium manganese iron phosphate material achieves the optimal combination of the composite material in terms of space utilization and performance, and obtains a positive electrode material with high compaction, high energy density and excellent cycle performance.

[0134] (3) From the comparison between Examples 6 and 7 and Example 1, it can be seen that when the particles of the ternary single crystal material in the present invention are not within the preferred median particle size range, it is not conducive to improving the space utilization rate during mixing and affects the performance of the positive electrode material.

[0135] (4) It can be seen from Comparative Example 1 that the present invention adds ternary single crystal material to the traditional ternary polycrystalline mixed lithium manganese iron phosphate, which significantly improves the performance of the material and increases the compaction density.

[0136] (5) From the comparison of Comparative Examples 2 and 3 with Example 1, it can be seen that the overall particle size distribution of the lithium iron manganese phosphate material co-blended with the ternary polycrystalline and ternary single crystal materials becomes wider, which significantly improves the compaction density and cycle performance of the material; however, when the particle size distribution of the incorporated ternary single crystal material is not appropriate, the filling effect cannot be achieved by the different particle size distribution of the material, which directly leads to a decrease in the compaction density, thereby affecting the electrical properties of the material.

[0137] In summary, the particle size distribution of the ternary single crystal material in the present invention is between the large particles of the ternary polycrystalline material and the small particles of lithium iron manganese phosphate. After blending, the particle size distribution of the material is wider, and particles with relatively small particle sizes can fill the gaps between the large particles, which improves the compaction density of the material to a certain extent; according to the particle size distribution, the overall particle size distribution of the lithium iron manganese phosphate material co-blended with the ternary polycrystalline and ternary single crystal materials becomes wider, which improves the stability of lithium ions entering and exiting the ternary material lattice during charging and discharging, provides elastic strain for the material when it is impacted by external forces, and thereby improves the safety and cycle performance of the material.

[0138] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A ternary co-blended lithium manganese iron phosphate material, characterized in that: The ternary co-blended lithium manganese iron phosphate material includes a ternary single crystal material, a ternary polycrystalline material and lithium manganese iron phosphate; The particle size distribution of the ternary single crystal material is between that of the ternary polycrystalline material and lithium manganese iron phosphate; The mass relationship among the ternary single crystal material, the ternary polycrystalline material and the lithium iron manganese phosphate in the ternary co-blended lithium iron manganese phosphate material is distributed according to the grading formula: C / (A+B)=α / (1-α), 0.5≤α<1, A / B=β / (1-β),0.6≤β<1, Wherein, A is the mass of ternary polycrystalline material, B is the mass of ternary single crystal material, and C is the mass of lithium manganese iron phosphate; The ternary single crystal material is prepared by the following method, which comprises: (a) mixing a nickel-cobalt-manganese hydroxide precursor, a lithium source and a first additive, and performing a first sintering to obtain a ternary single crystal first sintered material; The first additive includes any one of strontium carbonate, zirconium hydroxide or magnesium dioxide or a combination of at least two thereof; (b) mixing a ternary single crystal first sintering material and a second additive, and performing a second sintering to obtain a ternary single crystal material; The second additive includes any one of V2O5, magnesium silicate or zinc fluoride or a combination of at least two thereof; The ternary polycrystalline material is prepared by the following method, which comprises: Mixing nickel-cobalt-manganese hydroxide precursor, lithium source and additive materials, calcining at high temperature to obtain ternary polycrystalline material; The additive material includes any one of aluminum phosphate, niobium oxide or yttrium trioxide, or a combination of at least two of them.

2. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The median particle size of the ternary single crystal material is 4 to 7 μm.

3. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The particle size distribution of the ternary single crystal material is 0.3-0.

8.

4. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The median particle size of the ternary polycrystalline material is 10 to 20 μm.

5. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The particle size distribution of the ternary polycrystalline material is 0.8-1.

2.

6. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The median particle size of the lithium manganese iron phosphate is 1 to 2 μm.

7. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The particle size distribution of the lithium manganese iron phosphate is 0.2-0.

4.

8. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: Step (a) The temperature of the first sintering is 750-950°C.

9. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The first sintering time in step (a) is 10 to 15 hours.

10. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: Step (b) The second sintering temperature is 400-500°C.

11. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The second sintering time in step (b) is 3 to 6 hours.

12. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The temperature of the high temperature calcination is 750-950°C.

13. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The high temperature calcination time is 10 to 15 hours.

14. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The high temperature calcination further includes rolling, jaw crushing, pulverizing and screening.

15. The ternary co-blended lithium manganese iron phosphate material according to claim 1, characterized in that: The preparation method of lithium manganese iron phosphate comprises the following steps: (i) in a liquid phase system, mixing a lithium iron manganese phosphate precursor, a lithium source and a carbon source, and drying to obtain a lithium iron manganese phosphate precursor; (ii) Sintering in an inert gas atmosphere to obtain lithium iron manganese phosphate.

16. The ternary co-blended lithium manganese iron phosphate material according to claim 15, characterized in that: The drying in step (i) comprises spray drying.

17. The ternary co-blended lithium manganese iron phosphate material according to claim 15, characterized in that: The sintering temperature in step (ii) is 500-800°C.

18. The ternary co-blended lithium manganese iron phosphate material according to claim 15, characterized in that: The sintering time in step (ii) is 5 to 18 hours.

19. The ternary co-blended lithium manganese iron phosphate material according to claim 15, characterized in that: The lithium iron manganese phosphate is carbon-coated lithium iron manganese phosphate.

20. A method for preparing the ternary co-blended lithium manganese iron phosphate material according to any one of claims 1 to 19, characterized in that: The preparation method comprises the following steps: According to the grading formula, the ternary single crystal material, the ternary polycrystalline material and the lithium iron manganese phosphate are mixed to obtain the ternary co-blended lithium iron manganese phosphate material; The gradation formula is: C / (A+B)=α / (1-α), 0.5≤α<1, A / B=β / (1-β), 0.6≤β<1.

21. A positive electrode sheet, characterized in that: The positive electrode sheet contains the ternary co-blended lithium manganese iron phosphate material as described in any one of claims 1-19.

22. A battery, characterized in that: The battery contains the ternary co-blended lithium manganese iron phosphate material as described in any one of claims 1-19.

Citation Information

Patent Citations

  • Positive electrode plate and lithium ion battery

    CN110660961A

  • Low-temperature rate type power lithium ion battery and preparation method thereof

    CN113178623A

  • Lithium ion battery positive plate, preparation method thereof and lithium ion battery

    CN113948673A

Cited By

  • Lithium manganese iron phosphate composite material coated with lithium titanium aluminum phosphate, preparation method of lithium manganese iron phosphate composite material and lithium ion battery

    CN121726376A

  • A lithium aluminum titanium phosphate-coated lithium iron manganese phosphate composite material, a preparation method thereof, and a lithium ion battery

    CN121726376B